Recurrent axillary artery thrombosis due to myocardial infarction - Kumar, Sathish; Sayyed, Azhar (International Surgery Journal, 2022)
Left ventricular thrombus is a fatal complication of acute myocardial infarction as it can cause systemic thromboembolism. One of the most feared complications is the occurrence of thromboembolic events due to dislodgment left ventricular thrombus. Here we reported a case of 47 year old male patient who presented with recurrent axillary artery thrombosis. On evaluation he was found to have regional wall motion abnormality of left ventricle in echocardiography which caused left ventricle thrombus leading to systemic thromboembolic events. It is always essential to evaluate cardiac cause by an transthoracic echocardiography in case of recurrent thromboembolic events.